A fluorescent probe based on novel fused four ring quinoxalinamine for palladium detection and bio-imaging. (19th November 2020) - Zhang, Yong; Yang, Min; Ji, Min
Abstract : An "off–on" fluorescent probe was designed to detect palladium of all the typical oxidation states (0, +2, +4) without additional additives. Abstract : A fluorescent probe based on the Tsuji–Trost reaction was developed for detecting palladium species of all the typical oxidation states (0, +2, +4). In this probe, a novel fused four-ring quinoxalinamine was firstly designed as the fluorophore. The probe displayed high selectivity towards palladium with a distinct color change in aqueous media. Non-toxic and water-soluble PEG400 was used to replace the phosphine ligands and the reducing agents. In the absence of PEG400, the probe could discriminate Pd(0) from Pd(ii ) and Pd(iv ) in solutions. The actual water sample detection and bio-imaging results indicated the probe's great potential for palladium detection in both solutions and living systems.